Language used in drama at the end of the twentieth century (a textual analysis of works by Jon Fosse and their place in the Scandinavian context) - Stehlíková, Karolína, 1975- (2006)
The aim of this thesis is to trace the evolution of dramatic text at the end of the twentieth century with regard to the work of Jon Fosse, the contemporary Norwegian playwright. In the introduction chapter the author attempts to trace some of the significant trends that are to be found in contemporary European drama. The second chapter is devoted to the boom in Scandinavian drama. Chapter 3 is devoted entirely to Jon Fosse (his backround, his place in various contexts, characteristics of his dramatic style). In the penultimate chapter, the shifts that are traceable in the dramatic structure of Fosse's texts are being explored. The fifth chapter centres on particular problems relating to the translation of contemporary drama (with particular respect to Jon Fosse's plays).